The PD1/PDL1 axis, a promising therapeutic target in aggressive breast cancers. (3rd March 2016) - Bertucci, François; Finetti, Pascal; Birnbaum, Daniel; Mamessier, Emilie
ABSTRACT: Analysis of PDL1 mRNA expression in ∼5, 500 breast cancers showed PDL1 upregulation in 38% of basal tumors and 38% of inflammatory breast cancers (IBC). Upregulation, associated with signs of strong cytotoxic local immune response, was associated with a better survival in the basal or triple-negative subtypes, and with a better pathological response to chemotherapy in these subtypes and IBC. Reactivation of dormant tumor-infiltrating lymphocytes (TILs) by PD1/PDL1-inhibitors represents a promising strategy in these aggressive tumors.